THE EFFECT OF ESTAFET WRITING ON STUDENTS’ WRITING PROCEDURE TEXT (A STUDY AT THE TWELVETH GRADE OF SMKS TI PUTRA HARAPAN 2 2020-2021 ACADEMIC YEAR) - Mestina Mesi Waruwu (JURNAL LINER (Language Intelligence and Educational Research), 2020)
Waruwu, Mestina. 2020. The Effect of Using Estafet Writing at the twelve Grade of SMKS TI Putra Harapan 2. Skripsi, Program Studi Pendidikan Bahasa Inggris. Institut Pendidikan Tapanuli Selatan Padang Sidimpuan. ABSTRACT The aim of this research are to know: 1) the application of estafet writing on teaching writing procedure text ability, 2) the students writing procedure text ability before and after using estafet writing , 3) Whether there is any significant effect of estafet writing on teaching writing procedure text ability at the twelve Grade Students of SMKS TI Putra Harapan 2. This research uses experimental method with the pre-experimental design by using one-group pretest and posttest design. The population of this research was all of the XII grade students’ of SMKS TI Putra Harapan 2 which consist of 37 students. Sample were XII TKJ which consist of 22 students which taken by purposive sampling. In collecting the data the researchers uses observation sheet and test as an instrument. The result of this research: 1) the application of Estafet writing was 3.4, it is categorized “Very Good”. 2) the mean score of the students’ writing procedure text ability was 50,83 and it was categorized “fail”. Meanwhile, after using complete sentence model was 81,3, it is categorized “good”. The result of data analysis shows that ttest was higher than ttable (ttest 23,28> ttable 2.08). So, the hypothesis was accepted. It means that, there is any significant effect of estafet writing on students’ writing procedure text ability at the XII grade students of SMKS TI Putra Harapan 2. Keywords: Estafet Writing, Writing Procedure Text Ability